EFFECTIVENESS OF EXTENSION ACTIVITIES ON FISH FARMERS GROUP IN THE NAGARI SUNGAI ANTUAN DISTRICT OF MUNGKA SUBDISTRICT LIMAPULUH KOTA WEST SUMATRA PROVINCE - Wanti, Desselvy; Nugroho, Firman; ', Kusai (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
This research was conducted in September 2014 which took place in Nagari Sungai Antuan District of Mungka subdistrict Limapuluh kota West Sumatra province. The population is fish farmers as much as 20 people, and 1 extension. So the method of sample collections using the census method.Extension officers visit the fish farmers in the Nagari Sungai Antuan carried out 3-4 times a month, according to the needs of fish farmers. Of the three elements of behaviour change can be seen that fisheries extension activities in the Nagari Sungai Antuan in groups of fish farming in ponds has been effective. It can be seen from each element of behaviour change, the element of